Identification of Close Modes on Frequency in Rotating Systems - Rafael A. Figueroa-Díaz (MDPI AG, 2021)
In the area of modal balancing, it is essential to identify the vibration modes to be balanced in order to obtain the different modal parameters that will allow knowing the correction weight and its position in the balance planes. However, in some cases, a single mode is apparently observed in the polar response diagrams used for this process, which actually contains at least two modes and which, when added vectorially, shows only one apparent mode. In these cases, in addition to the intrinsic errors when using a modal parameter extraction tool, there will be errors in determining the correction weight for the modes, as well as for the placement angle. In this work, an identification methodology is presented which, through the use of coordinate transformation and a modal parameter extraction tool, allows identifying characteristic patterns of close modes in frequency and which, when applied in the study of a system in the field, offers robustness and applicability.